Pemetaan Daerah Rawan Gempabumi Berdasarkan Nilai Parameter Kerapuhan Batuan Dan Peak Ground Acceleration(PGA) Di Wilayah Bali - Komang Ngurah Suarbawa; IGA Putra Adnyana; Amalia Dwi Lestari (Universitas Hamzanwadi, 2024)
Bali is a region that is prone to earthquake hazards. This is because Bali is flanked by two earthquake-causing zones, first is the subduction zone in the south and thesecond one is back arc fault zone in the north. One of the efforts to minimize damage or loss caused by earthquakes is to anal yze the vulnerability of a region to earthquakes. In this study, the earthquakeparameters used as hazard indicators were the level of rock fragility (b-value) and peak ground acceleration (PGA). Based on the results of the b-value calculation byusing the Maximum Likelihood method, therock fragility level for Bali region is obtained from 0.370 to 1.419. Whilethe results of PGA calculation by using two empirical methods, there are the M.V. Mickeymethodand the Lin Wu method show that the M.V. Mickey method is more suitable for use in the Bali area. Based onthe results of PGA calculation by using the M.V. Mickey method obtained the PGA value for the Bali region is obtained from 517.32-828.58 gal. So based on theresults of the analysis of the b-value and PGA parameters, it was found that the area of Bali that is prone to earthquakes is the western part of Buleleng Regency and most of Jembrana Regency.